Penerapan Problem Based Learning Berbasis STEM untuk Meningkatkan Kemampuan Penalaran Matematis Siswa SMP di Era Abad 21 - Muhammad Bayu Prayoga; Isnaeni Umi Machromah (Universitas Muhammadiyah Magelang, 2026)
This study was conducted to analyze the extent to which the implementation of the Problem-Based Learning (PBL) model integrated with the STEM approach has an impact on the mathematical reasoning abilities of junior high school students, particularly in the subject of Two-Variable Linear Equation Systems (SPLDV). This study applied a quantitative approach using a quasi-experimental method and a pretest-posttest design with a control group. The research subjects were divided into two class groups, namely class VIII B as the experimental group that received learning through the STEM-based PBL model, while class VIII A acted as the control group that followed the learning process using conventional methods. The data collection tool used was an essay-type test, which was used to evaluate the level of students' mathematical reasoning abilities through the implementation of a pretest and posttest. Data processing and analysis were carried out using a series of statistical tests, including normality tests, homogeneity tests, Independent Sample t-tests, Paired Sample t-tests, and N-Gain calculations to determine the level of improvement in learning outcomes. The research findings showed that the average posttest scores of students in the experimental group were higher than those in the control group. Based on the results of the Independent Sample t-test, it was found that there was a significant difference in mathematical reasoning ability between the two groups. Meanwhile, the results of the Paired Sample t-test indicated a significant increase in mathematical reasoning ability in the experimental group after the implementation of the Problem-Based Learning (PBL) model combined with the STEM approach. In addition, the N-Gain calculation results show that the level of improvement in mathematical reasoning ability in the experimental group is categorized as less effective, although the improvement value is still higher than that of the control group. Therefore, the application of the STEM-based PBL model can be considered as an alternative learning strategy that has the potential to help develop students' mathematical reasoning abilities